A new oriental species of Thecophora Rondani (Diptera: Conopidae) and first records of Thecophora caenovalva (Kröber) from Japan - Stuke, Jens-Hermann (Contributions to Entomology = Beiträge zur Entomologie, 2017)
Thecophora bartaki spec. nov. is described from Laos and Thecophora caenovalva (Kröber) is reported from Japan.Nomenclatural ActsThecophora bartaki spec. nov. – urn:lsid:zoobank.org:act:D0069884-865A-46CC-92EE-DE874AA6EDD6